(untitled) (CIPEEX, 2025)
Introduction: Antimicrobial resistance (AMR) is regarded as one of the greatest threats to global public health and, in Brazil, already constitutes an emerging challenge for the Unified Health System (SUS). It is estimated that AMR is directly responsible for approximately 34,000 deaths and associated with over 138,000 additional deaths annually in the country, totaling around 221,000 deaths from bacterial infections and 400,000 cases of sepsis recorded each year (Brazil, 2023). Beyond its clinical impact, resistance increases hospital costs, overloads health services, and compromises patient safety. In this context, understanding the epidemiological landscape of AMR is essential to inform public policies, surveillance measures, and rational antimicrobial use protocols. Objective: To describe the current situation of antimicrobial resistance in Brazil based on data and reports from the Ministry of Health, highlighting its impact on the SUS, the main microorganisms involved, the ongoing response policies, and perspectives for improving clinical and public health management. Method: This is an observational and descriptive study based on secondary data and oficial documents from the Ministry of Health. Reports from the National Action Plan for the Prevention and Control of Antimicrobial Resistance (PAN-BR), epidemiological bulletins available on the Ministry of Health’s Virtual Health Library (BVS MS) platform, and data consolidated by GLASS-BR— the Brazilian surveillance system integrated into the World Health Organization’s Global Antimicrobial Resistance Surveillance System—were consulted. Public data from DATASUS, SIH/SUS, and SIM concerning hospitalizations, deaths, and notifications related to antimicrobial resistance were also used. Because these are public and anonymized data, submission to a Research Ethics Committee was not required, in accordance with Resolution No. 510/2016 of the National Health Council. Results: The analyzed data reveal a progressive increase in antimicrobial resistance rates across various regions of the country. Klebsiella pneumoniae showed resistance exceeding 50% to diferent antimicrobials, with up to 8% of strains resistant to carbapenems—drugs of last resort (Brazil, 2022). Escherichia coli displayed high levels of resistance to fluoroquinolones, while Neisseria gonorrhoeae showed growing resistance to widely used antimicrobials in the treatment of sexually transmitted infections. In response, PAN-BR has structured intersectoral strategies under the One Health approach, encompassing human, animal, and environmental health. The National Program for the Control of Healthcare-Associated Infections (PNCPIRAS) strengthens hospital protocols, and the National Network of Public Health Laboratories (Lacen) supports laboratory surveillance. Furthermore, the National List of Essential Medicines (Rename), together with the WHO AWaRe classification, and the National Committee for the Rational Use of Medicines (CNPURM) guide clinical practices and access policies (WHO, 2022). Conclusion: Antimicrobial resistance represents an urgent challenge for the SUS, requiring continuous epidemiological surveillance, ongoing education for healthcare professionals, and investments in laboratory infrastructure. National data underscore the need to expand adherence to prevention protocols, promote the rational use of antibiotics, and strengthen the surveillance network. This characterization, based on oficial data from the Ministry of Health and DATASUS, provides evidence to support the formulation of public policies, the improvement of care quality, and the enhancement of patient safety, in alignment with international recommendations.